PHILOSOPHICAL VALUE OF SUMANGET KA-SUMEDANGAN IN EFFORTS TO DEVELOP STUDENTS' CHARACTER IN SUMEDANG REGENCY - Mochamad Ikbal Fawzi; Enok Maryani (Jurnal Cakrawala Pendas, 2024)
The cultivation of local culture and wisdom is important as an effort to minimize the impact of globalization on elementary school students. Sumanget Ka-Sumedang is one of the cultural heritages in the form of ideas or concepts from the Sumedang regency. This research would to analyze the philosophical value of Sumanget Ka-sumedangan in an effort to instill the character of students in Sumedang Regency. This research was conducted using a qualitative approach with a case study method. The data collection techniques in this study used interview techniques, observation, literature study, and documentation study. This research employs qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that out of the 7 schools examined in the study, one school implemented a program oriented towards the philosophical values of Sumanget Ka-Sumedang comprehensively. Other schools carried out activity programs without being based on Sumanget Ka-Sumedang, although there were still aspects of character value development present. The predominant types of activities chosen for implementation were through habituation and school culture. Philosophically, Sumanget Ka-Sumedang portrays the ideal Sumedang community, where individuals possess traits such as optimism, critical thinking, spiritual integrity, discipline, intelligence, politeness, and patience. Despite its longstanding existence, Sumanget Ka-Sumedang remains relevant to the challenges faced by the community today. The implementation of activity programs in educational units oriented to the philosophical values of Sumanget Ka-Sumedangan is the right way to instill the character of students.